PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN - Sayful Amrin; Damianus Tola; Agnes E. Wula (Bajang Institute, 2024)
This research aims to see the influence of digital marketing on decisions to purchase ornamental plants at Elmonik as a planting medium. This type of quantitative research uses data collection techniques using observation, documentation and questionnaires on consumers of Elmonik planting media. The research results show: (1) Digital marketing shows a value of 82.2%; (2) Purchasing decisions show a value of 82.6%; So it can be said that there is an influence of digital marketing on plant purchasing decisions. The hypothesis calculation is that Ha is accepted and Ho is rejected with a significant value of 0.00, this means it is smaller than α= 0.05. The Rsquare value is 0.670 and the t test results show a value of 6.127> 2.1098, it can be said that there is a very strong influence. It can be concluded; (1) To plant business owners to be more innovative in packaging and promoting their products and provide a wide variety of the newest types of ornamental plants; (2) To potential consumers to always be careful when shopping or purchasing goods online and to pay more attention to whether the products posted are in accordance with actual conditions; (3) For further researchers to be able to develop this research by adding other independent variables in order to provide new colors in the research. The influence of digital marketing on purchasing decisions